Effects of Yoga Practice on Selected Physiological and Psychological Variables in Middle Age Women Feeling Stress - A. Suman Kumar, B. Gopal, B. Tirumalaiah (Mathematical Statistician and Engineering Applications, 2022)
In this study, subjects were selected based on prevalence of stress. A stress questionnaire developed by A. Suman Kumar (2022) was made available to 30 men and the completed questionnaires were analyzed to determine stress levels. From these stressed middle-aged women, researchers selected her 30 subjects by random sampling of her AP. The main criteria for selecting subjects were prevalence of stress and willingness to participate and complete the programmed training to make the results credible. Pupils' ages ranged from her 19 to her 22 years old. Training took place from 6:00 am to 7:00 am, five days a week, excluding Saturdays and Sundays, for six weeks. Subjects must eat before training.10 subjects underwent her SVET, SVDC training. Ten subjects were trained in his B.K.S. Iyengar style (his two groups above made up the experimental group). Ten subjects formed the control group.